Evidence and Lessons from Latin America (ELLA) - Harvey, Blane; Ensor, Jonathan; Garside, Ben; Woodend, John; Naess, Lars Otto; Carlile, Liz (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Evidence and Lessons from Latin America (ELLA) was established as a programme in 2009 by the UK Department for International Development (DFID) as a way to synthesise research and policy lessons from Latin America and discuss them with a global audience – as part of a responsible exit strategy from bilateral aid to the region. The DFID conception of ELLA was “extracting” lessons from LA for the rest of the world and the regional centres developed knowledge topics that were pushed out to a network that was set-up to discuss the issues.